2005
DOI: 10.1111/j.1945-5100.2005.tb00374.x
|View full text |Cite
|
Sign up to set email alerts
|

A meteorite impact crater field in eastern Bavaria? A preliminary report

Abstract: Abstract-Numerous circular depressions north of Burghausen in eastern Bavaria, with diameters ranging from meters to tens of meters in size and dispersed over an area of at least 11 × 7 km, are suspected to have an extraterrestrial origin since they resemble other small meteorite impact craters. The depressions are bowl-shaped, have high circularity and a characteristic rim. Most of them were formed in unconsolidated glacial gravels and pebbles intermixed with fine-grained sand and clay. Magnetic investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…From earthquakes it is known that liquefaction explosion can produce perfectly circular craters [3,9] that sometimes are reminiscent of smaller craters in the Chiemgau impact strewn field. While in the Chiemgau area many craters show clear impact signature like melt rocks, shock effects and distinct geomagnetic anomalies [36,[51][52][53] others do not. Hence, the possibility that both meteorite impact and liquefaction craters may exist in and contribute to the crater-strewn field may not completely be excluded and has yet to be verified.…”
Section: Discussionmentioning
confidence: 99%
“…From earthquakes it is known that liquefaction explosion can produce perfectly circular craters [3,9] that sometimes are reminiscent of smaller craters in the Chiemgau impact strewn field. While in the Chiemgau area many craters show clear impact signature like melt rocks, shock effects and distinct geomagnetic anomalies [36,[51][52][53] others do not. Hence, the possibility that both meteorite impact and liquefaction craters may exist in and contribute to the crater-strewn field may not completely be excluded and has yet to be verified.…”
Section: Discussionmentioning
confidence: 99%
“…The authors [53] stated that silicides, mainly xifengite and gupeiite, were found in the region even more than 20 cm below the undisturbed forest soil surface, or in such archaeological situations which would preclude recent industrial origin. Other authors, however, denied the preferential occurrence of silicides in craters as well as their presence in deeper soil horizons, and pointed to the chemical and isotopic compositions and large particle size inconsistent with cosmic origin of the silicides [54,55].…”
Section: Unusual Impactor Rich In Iron Silicides?mentioning
confidence: 99%
“…The fragmentation of a single body as suggested by [53] and [12] to explain the elongate "Chiemgau-Impact strewn field" is problematic (see also [55]). Nevertheless, a smaller strewn field at Burghausen, including both craters at Emmerting [7,61], may be realistic, especially in the case of a 'rubble-pile'-like impactor. The assumption that many small asteroids have such a "loose" consistence has been confirmed by spacecraft missions (e.g., [62]).…”
Section: 33' Rubble Pile' Impactor?mentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike Kaali and Wabar, which are accepted as extraterrestrial in origin, the origin of the Sirente craters has been contested, with the suggestion that these circular, lake-filled craters are no more than artificial lakes for watering livestock (Speranza et al, 2004). Similarly, the Burghausen/ Chiemgau crater field in south Germany is still under discussion despite highly persuasive evidence for exotic chemistry at the site (Fehr et al, 2005).…”
Section: The Issue Of Craters and Crater Fieldsmentioning
confidence: 99%